STUDIES ON THE AGE AND GROWTH OF LABEO CALBASU (HAMILTON) WITH AN EXPLOITATION PATTERN FROM THE GANGA RIVER SYSTEM, UTTAR PRADESH (INDIA} - Dwivedi, Amitabh Chandra; Anupama, Anupama; Bisht, Bhawana; Khan, Shakila (Journal of Indian Fisheries Association, 2009)
Samples were collected to study the age and growth of Labeo calbasu {Hamilton) from the river Ghaghra {Guptarghat centre, Faizabad). The scales of L. calbasu have been used for age and growth studies in present paper. Study of the marginal rings on the scales of L. calbasu indicates their annual nature. The fish attained growth in 1st 18.7 em, 2"d 27.8 em, 3'd 35.7 em, 4th 41.8 em, 5th 46.9 em, 6th 54.9 em and ih 57.4 em years of the life. The growth rate was observed 18.7, 9.1, 7.9, 6.7, 5.1, 8.0 and 2.5 em for 1st to ih age classes respectively. The age groups 1+ to 4+ constituted 91.17% of the total exploited population and 8.83% of remaining age groups {5+ to 7+). The maximum exploited population was observed in 2+ age group with 33.68%. Overall exploitation pattern was systematic and a good indicator for heavy recruitment.Key words: Age, Growth rate, Exploitation, Recruitment, Ghaghra river, Labeo calbasu.